Thực trạng tổ chức bồi dưỡng năng lực công nghệ số cho giáo viên ngoại ngữ ở trường trung học phổ thông - Hà Thanh Hương, Hà Thanh Hương (Tạp chí Giáo dục, 2026)
In the context of Vietnam's education system, accelerating digital transformation to meet the requirements of curriculum reform and international integration, developing digital technology skills for teachers, especially foreign language teachers in high schools, is considered a key task. This paper focuses on developing a training program to enhance digital technology skills among foreign language teachers, based on an analysis of relevant theoretical approaches, references to international competency frameworks, and practical surveys conducted in general education institutions. The survey results indicate that teachers have a relatively comprehensive understanding of the role of digital technology in teaching, but still face difficulties in designing digital learning materials, using learning management systems, and employing online assessment tools. Based on these results, the paper proposes a training program comprising four core components: equipping teachers with knowledge of digital transformation in education; developing skills in applying technology in foreign language teaching; improving data management and security capabilities; and fostering creative thinking and adaptability to innovation. The program is designed to be flexible, combining in-person and online formats, thereby improving the quality of teaching and promoting innovation in general education.